The Influence of Implementing Realistic Mathematics Learning Model on The Mathematics Learning Outcomes - Alvi Sahrin Nasution; Wirna Arifitriana; Rizky Febriani Pohan (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2024)
The low learning outcomes of students at Nurul Ilmi Padangsidimpuan Private Junior High School in learning mathematics are caused by implementation of conventional learning processes so that students become passive and do not participate in the learning process. For this reason, the Realistic Mathematics Learning (RML) model was chosen as a solution to overcome the problem of low student learning outcomes. This study aims to determine whether there is an increase in the mathematics learning outcomes of class VII students at Private Junior High School Nurul Ilmi Padangsidimpuan in material of linear equations through the RML model and to determine the effectiveness of the RML model on mathematics learning outcomes. The method used in this study is a quasi-experimental method using a pretest-posttest control group research design. The research subjects were class VII students of Private Junior High School Nurul Ilmi Padangsidimpuan Semester I of the 2022/2023 Academic Year with a total of 30 students. The data collection technique was carried out by testing using multiple choice questions of 20 validated questions. Data analysis techniques are quantitative descriptive analysis and inferential analysis. The increase in mathematics learning outcomes for each group was calculated using N-gain analysis and the percent effectiveness of the RML model was calculated by comparing it to conventional learning models. Based on the results of the study, it was found that the RML model had an effect on the mathematics learning outcomes of class VII students at Nurul Ilmi Padangsidimpuan Private Junior High School. The increase in the mathematics learning outcomes of the experimental group was 43.84% and the control group was only 37.5%. So that the results of learning mathematics in the experimental group is better than the control group. The RML model has an effectiveness percentage of 6.67% for improving mathematics learning outcomes for class VII students of Private Junior High School Nurul Ilmi Padangsidimpuan. Thus, the application of the RML model is very suitable and effective for learning mathematics at the junior high school level.